Point-corrosion-resistant nuclear-grade duplex stainless steel welding rod as well as preparation method and application thereof

By coating specific skins on the outer wall of the core of the nuclear-grade duplex stainless steel electrode and baking treatment, the problem of lack of pitting corrosion-resistant nuclear-grade duplex stainless steel electrodes in the prior art is solved, and the excellent tensile performance of the welding rod is achieved , impact toughness and pit corrosion resistance.

CN119426847APending Publication Date: 2025-02-14HARBIN WELL WELDING CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411712979.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art lacks nuclear-grade duplex stainless steel welding rods that have excellent tensile properties and impact toughness while also having pit corrosion resistance.

Method used

The ER2209 welding core is used and a medicine skin is coated on its outer wall. The medicine skin is composed of marble, fluorite, ice crystal, rutile, etc., and ferrochromium nitride is added to prepare pit corrosion resistance through low-temperature baking and high-temperature baking. nuclear-grade duplex stainless steel welding rod.

Benefits of technology

The welding rod not only has excellent tensile performance and impact toughness, but also has excellent pit corrosion resistance, which can effectively reduce the influence of hydrogen, prevent the occurrence of defects such as weld cracks and sand holes, and has excellent full-position welding process performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156215120000051
    Figure BDA0005156215120000051
Patent Text Reader

Abstract

The invention discloses a pitting-corrosion-resistant nuclear-grade duplex stainless steel welding rod and a preparation method and application thereof. The invention belongs to the technical field of welding. The nuclear-grade duplex stainless steel welding rod solves the problem that nuclear-grade duplex stainless steel welding rods with excellent tensile property, impact toughness and pitting corrosion resistance are lacked in the prior art. The pitting-corrosion-resistant nuclear-grade duplex stainless steel electrode comprises the core wire and the coating coated on the outer wall of the core wire, the pitting-corrosion-resistant nuclear-grade duplex stainless steel electrode has strong desulfurization and dephosphorization capabilities, the coating has a dehydrogenation effect, the room-temperature tensile strength exceeds 690 MPa, the room-temperature percentage elongation after fracture exceeds 20%, the-40 DEG C low-temperature impact is larger than 90 J, the pitting corrosion rate is smaller than 10 mdd, nitrided ferrochrome is added into the coating, and therefore the pitting corrosion resistance of the pitting-corrosion-resistant nuclear-grade duplex stainless steel electrode is greatly improved, and the service life of the pitting-corrosion-resistant nuclear-grade duplex stainless steel electrode is prolonged. And the contents of Cr and N are increased, so that the pitting corrosion resistance index of deposited metal can be improved. The special requirements for tensile property, impact toughness and pitting corrosion resistance of the nuclear power station welding rod can be fully met, so that the nuclear power station welding rod can be applied to the fields of nuclear power station construction and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of welding materials, and in particular relates to a pitting corrosion resistant nuclear-grade duplex stainless steel welding rod and a preparation method and application thereof. Background Art

[0002] Duplex stainless steel refers to a type of stainless steel that contains both austenite and ferrite structures, and the two phases of structure need to exist independently, and the ferrite content needs to be at least 30%. This type of steel has the characteristics of both austenitic and ferritic stainless steels, has good resistance to stress corrosion and intergranular corrosion, high material strength, and low linear expansion coefficient, and can be connected with dissimilar joints. Compared with ferrite, it has higher plasticity and toughness, no room temperature brittleness, significantly improved intergranular corrosion resistance and welding performance, while maintaining the 475℃ brittleness and high thermal conductivity of ferritic stainless steel, and has the characteristics of superplasticity. Compared with austenitic stainless steel, it has high strength and significantly improved resistance to intergranular corrosion and chloride stress corrosion. Duplex stainless steel is also a nickel-saving stainless steel. Duplex stainless steel combines the advantages of austenitic stainless steel and ferritic stainless steel, which can reduce the use of materials in construction, thereby reducing costs. It is precisely because of these advantages that duplex stainless steel is more and more widely used in the construction of nuclear power plants.

[0003] The construction of the third-generation nuclear power plant adopts a safer and more advanced third-generation nuclear power unit. In order to meet the construction and application conditions with such high design and strict requirements, it is urgent to develop welding rod materials that improve other conditions on the basis of unchanged or better tensile properties and impact toughness. At present, most of the research on the corrosion resistance of welding rods is done, but there is a lack of research and attention on pitting corrosion resistance. In summary, in order to meet the needs of the rapid development of existing nuclear power projects, the development of a nuclear-grade duplex stainless steel welding rod with excellent tensile properties, impact toughness and pitting corrosion resistance is of great significance to the construction of nuclear power projects. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that there is a lack of nuclear-grade duplex stainless steel welding rods with excellent tensile properties and impact toughness and pitting corrosion resistance in the prior art. The present invention provides a nuclear-grade duplex stainless steel welding rod with pitting corrosion resistance and a preparation method and application thereof.

[0005] The technical solution of the present invention is as follows:

[0006] One of the purposes of the present invention is to provide a nuclear-grade duplex stainless steel welding rod resistant to pitting corrosion, comprising a welding core and a coating coated on the outer wall of the welding core, wherein the welding core is ER2209, and the coating has the following components in weight percentage:

[0007] Marble: 20-32%, fluorite: 5-15%, cryolite: 16-26%, rutile: 10-20%, titanium dioxide: 1-5%, quartz: 1-5%, alumina: 1-3%, ferrosilicon: 0-0.5%, electrolytic manganese: 0-2%, metallic chromium: 1-4%, nickel powder: 1-4%, ferrochrome nitride: 2.5-6%, soda ash: 0.5-1%, and the balance is iron powder.

[0008] It is further defined that the mass fraction of the chemical composition of ferrochromium nitride in the coating is 3.0-3.8% N + 62.0-66.0% Cr.

[0009] A second object of the present invention is to provide a method for preparing a nuclear-grade duplex stainless steel welding rod resistant to pitting corrosion, the method comprising:

[0010] Preparation of flux coating: weigh marble, fluorite, cryolite, rutile, titanium dioxide, quartz, alumina, ferrosilicon, electrolytic manganese, metallic chromium, nickel powder, ferrochromium nitride and soda ash, and mix them to obtain welding rod flux powder;

[0011] Preparation of welding rod: The welding rod coating powder and the binder are mixed evenly to obtain a mixture, and then the mixture is coated on the welding core, and then low-temperature baking and high-temperature baking are performed in sequence to obtain a nuclear-grade duplex stainless steel welding rod resistant to pitting corrosion.

[0012] It is further defined that the binder is pure sodium water glass.

[0013] It is further defined that the modulus of pure sodium water glass is 2.6 to 3.0.

[0014] It is further specified that the mass ratio of pure sodium water glass to the coating is 1:2 to 6.

[0015] It is further specified that the mass ratio of pure sodium water glass to the coating is 1:4.

[0016] It is further limited that the low-temperature baking temperature is 90-110°C, the insulation time is 4-6 hours, and the high-temperature baking temperature is 340-360°C, and the insulation time is 2-4 hours.

[0017] It is further defined that the welding rod diameter is Φ2.5-5.0 mm.

[0018] A third object of the present invention is to provide an application of the above-mentioned nuclear-grade duplex stainless steel welding rod resistant to pitting corrosion in the construction of nuclear power plants.

[0019] Compared with the prior art, the advantages of the present invention are as follows:

[0020] (1) The pitting corrosion resistant nuclear-grade duplex stainless steel welding rod prepared by the present invention belongs to a low-hydrogen alkaline slag welding rod, has a strong desulfurization and dephosphorization ability, and the coating has a dehydrogenation effect, which can effectively reduce the influence of hydrogen during the welding process, thereby reducing the hydrogen content in the weld and preventing the occurrence of defects such as weld cracks and sand holes.

[0021] (2) The deposited metal of the pitting corrosion resistant nuclear-grade duplex stainless steel electrode prepared by the present invention has a room temperature tensile strength of more than 690 MPa, a room temperature elongation of more than 20%, a -40°C low-temperature impact of more than 90 J, a pitting corrosion rate of less than 10 mdd, and the electrode has excellent all-position welding process performance.

[0022] (3) The welding rod is easy to precipitate more chromium carbide when used, and the local chromium content decreases, resulting in a decrease in corrosion resistance and mechanical properties. The nuclear-grade duplex stainless steel welding rod resistant to pitting corrosion provided by the present invention has ferrochromium nitride added to the coating. On the one hand, it can increase the Cr content, and on the other hand, it can increase the N content, which can improve the pitting corrosion resistance index of the deposited metal (PREN = Cr% + 3.3Mo% + 16N%). The larger the pitting corrosion resistance index, the stronger the pitting corrosion resistance of the deposited metal. The welding rod prepared by the present invention can ensure that PREN is greater than 35 on the basis of excellent tensile properties and impact toughness, and the pitting corrosion rate can be stably <10mdd, and has excellent pitting corrosion resistance. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0025] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0026] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0027] The following are the materials used in the experiment:

[0028] The welding core is ER2209, and its chemical composition and mass percentage are C: 0.02%, Si: 0.51%, Mn: 1.78%, S: 0.004%, P: 0.021%, Cr: 23.01%, Ni: 8.66%, Mo: 3.21%, Cu: 0.07%, Co: 0.02%, N: 0.11%, and the balance is Fe.

[0029] Embodiment 1:

[0030] Preparation of coating: weigh 28% marble, 12% fluorite, 20% cryolite, 18% rutile, 2% titanium dioxide, 3% quartz, 2% alumina, 0.5% ferrosilicon, 1% electrolytic manganese, 2% metallic chromium, 2% nickel powder, 6% ferrochromium nitride, 1% soda ash, and the balance is iron powder, mix well to obtain welding rod coating powder;

[0031] Preparation of welding rod: The prepared welding rod coating powder and pure sodium water glass with a modulus of 2.7 are mixed evenly in a mass ratio of 4:1 to obtain a mixture, and then the mixture is coated on the ER2209 welding core by a press coater, and then low-temperature baking at a temperature of 100°C for 5 hours, high-temperature baking at a temperature of 350°C for 3 hours, and finally a nuclear-grade duplex stainless steel welding rod with a diameter of Φ4.0 mm and resistance to pitting corrosion is obtained.

[0032] Embodiment 2:

[0033] Preparation of coating: weigh 28% marble, 12% fluorite, 20% cryolite, 18% rutile, 2% titanium dioxide, 3% quartz, 2% alumina, 0.5% ferrosilicon, 1% electrolytic manganese, 2% metallic chromium, 2% nickel powder, 4% ferrochrome nitride, 1% soda ash, and the balance iron powder, and mix them evenly to obtain welding rod coating powder;

[0034] Preparation of welding rod: The prepared welding rod coating powder and pure sodium water glass with a modulus of 2.7 are mixed evenly in a mass ratio of 4:1 to obtain a mixture, and then the mixture is coated on the ER2209 welding core by a press coater, and then low-temperature baking at a temperature of 100°C for 5 hours, high-temperature baking at a temperature of 350°C for 3 hours, and finally a nuclear-grade duplex stainless steel welding rod with a diameter of Φ4.0 mm and resistance to pitting corrosion is obtained.

[0035] Comparative Example 1:

[0036] Preparation of coating: weigh 28% marble, 12% fluorite, 20% cryolite, 18% rutile, 2% titanium dioxide, 3% quartz, 2% alumina, 0.5% ferrosilicon, 1% electrolytic manganese, 2% metallic chromium, 2% nickel powder, 1% soda ash, and the balance iron powder according to mass fraction, mix well to obtain welding rod coating powder;

[0037] Preparation of welding rod: The prepared welding rod coating powder and pure sodium water glass with a modulus of 2.7 are mixed evenly in a mass ratio of 4:1 to obtain a mixture, and then the mixture is coated on the welding core by a press coater, and then low-temperature baking at a temperature of 100°C for 5 hours, high-temperature baking at a temperature of 350°C for 3 hours, and finally a nuclear-grade duplex stainless steel welding rod with a diameter of Φ4.0 mm is obtained.

[0038] Comparative Example 2:

[0039] Preparation of coating: weigh 28% marble, 12% fluorite, 20% cryolite, 18% rutile, 2% titanium dioxide, 3% quartz, 2% alumina, 0.5% ferrosilicon, 1% electrolytic manganese, 2% metallic chromium, 2% nickel powder, 2% ferrochrome nitride, 1% soda ash, and the balance is iron powder, mix well to obtain welding rod coating powder;

[0040] Preparation of welding rod: The prepared welding rod coating powder and pure sodium water glass with a modulus of 2.7 are mixed evenly in a mass ratio of 4:1 to obtain a mixture, and then the mixture is coated on the welding core by a press coater, and then low-temperature baking at a temperature of 100°C for 5 hours, high-temperature baking at a temperature of 350°C for 3 hours, and finally a nuclear-grade duplex stainless steel welding rod with a diameter of Φ4.0 mm is obtained.

[0041] The electrodes in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were welded using the welding process parameters shown in Table 1, and the obtained deposited metals were tested for mechanical properties and pitting corrosion resistance.

[0042] Table 1 Electrode welding process parameters

[0043] Welding current (A) Arc voltage(V) Welding speed (mm / min) Inter-pass temperature (℃) 145 24~26 200 100~120

[0044] The mechanical properties and pitting corrosion resistance of the deposited metals obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were tested under the following test conditions: the impact property test of the deposited metal was carried out in accordance with the provisions of GB / T2650-2015 standard, the tensile property test of the deposited metal was carried out in accordance with the provisions of GB / T2652-2015 standard, and the pitting corrosion resistance test of the deposited metal was carried out in accordance with the provisions of ASTMA923C method. The specific results are shown in Table 2.

[0045] Table 2 Mechanical properties and pitting corrosion resistance of deposited metal

[0046]

[0047] It can be seen from Table 2 that the mechanical properties of the deposited metal of the pitting corrosion resistant nuclear-grade duplex stainless steel welding rods of Example 1 and Example 2 meet the requirements of the nuclear-grade technical conditions, and the pitting corrosion resistance also meets the requirements of the nuclear-grade technical conditions. The room temperature tensile strength can reach 800MPa and above, the room temperature elongation after fracture can reach 25% and above, and the -40°C low-temperature impact KV2 can be stably greater than 90J, and the pitting corrosion resistance index (PREN=Cr%+3.3Mo%+16N%) of the pitting corrosion resistant nuclear-grade duplex stainless steel welding rods of Example 1 and Example 2 is greater than 35, and the pitting corrosion resistance rate is less than 10mdd, which meets the requirements of the nuclear-grade technical conditions; while the pitting corrosion resistance index (PREN=Cr%+3.3Mo%+16N%) of the nuclear-grade duplex stainless steel welding rods of Comparative Examples 1 and 2 is less than 35, and the pitting corrosion resistance index is greater than 10mdd, which does not meet the requirements of the nuclear-grade technical conditions. Therefore, the pitting corrosion resistant nuclear-grade duplex stainless steel welding rod prepared in the present application not only has excellent tensile properties and impact toughness but also has excellent pitting corrosion resistance.

[0048] In summary, the pitting corrosion-resistant nuclear-grade duplex stainless steel welding rod prepared by the present invention has both excellent tensile properties and impact toughness, as well as excellent pitting corrosion resistance. The welding rod prepared by the present invention also belongs to a low-hydrogen alkaline slag welding rod, which can effectively prevent the occurrence of defects such as weld cracks and sand holes during the welding process, and the welding rod has excellent all-position welding process performance.

[0049] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A pitting corrosion resistant nuclear grade duplex stainless steel welding rod, comprising a welding core and a coating coated on the outer wall of the welding core, characterized in that: The welding core is ER2209, and the coating has the following components by weight percentage: Marble: 20-32%, fluorite: 5-15%, cryolite: 16-26%, rutile: 10-20%, titanium dioxide: 1-5%, quartz: 1-5%, alumina: 1-3%, ferrosilicon: 0-0.5%, electrolytic manganese: 0-2%, metallic chromium: 1-4%, nickel powder: 1-4%, ferrochrome nitride: 2.5-6%, soda ash: 0.5-1%, and the balance is iron powder.

2. The pitting corrosion resistant nuclear grade duplex stainless steel welding rod according to claim 1, characterized in that: The mass fraction of the chemical composition of ferrochromium nitride in the coating is 3.0-3.8% N+62.0-66.0% Cr.

3. The method for preparing the pitting corrosion resistant nuclear grade duplex stainless steel welding rod according to claim 1 or 2, characterized in that: The method: Preparation of flux coating: weigh marble, fluorite, cryolite, rutile, titanium dioxide, quartz, alumina, ferrosilicon, electrolytic manganese, metallic chromium, nickel powder, ferrochromium nitride and soda ash, and mix them to obtain welding rod flux powder; Preparation of welding rod: The welding rod coating powder and the binder are mixed evenly to obtain a mixture, and then the mixture is coated on the welding core, and then low-temperature baking and high-temperature baking are performed in sequence to obtain a nuclear-grade duplex stainless steel welding rod resistant to pitting corrosion.

4. The method according to claim 3, characterized in that The binder is pure sodium water glass.

5. The method according to claim 4, characterized in that The modulus of pure sodium water glass is 2.6 to 3.

0.

6. The method according to claim 4, characterized in that The mass ratio of pure sodium water glass to coating is 1:2 to 6.

7. The method according to claim 6, characterized in that The mass ratio of pure sodium water glass to coating is 1:

4.

8. The method according to claim 3, characterized in that The low-temperature baking temperature is 90-110°C, and the insulation time is 4-6 hours. The high-temperature baking temperature is 340-360°C, and the insulation time is 2-4 hours.

9. The method according to claim 3, characterized in that: The diameter of the welding rod is Φ2.5-5.0mm.

10. Use of the pitting corrosion resistant nuclear grade duplex stainless steel welding rod according to claim 1 or 2 in the construction of nuclear power plants.

Citation Information

Cited By

  • Welding rod for welding duplex stainless steel and preparation method thereof

    CN120023525A